Bowel Endometriosis with Hemoperitoneum Complicating Pregnancy. Issue 4 (October 2013) - De Vincenzo, Rosa; Zannoni, Gian Franco; Ricci, Caterina; Conte, Carmine; Masciullo, Valeria
Case Report: We report a case of bowel endometriosis complicated by spontaneous hemoperitoneum and miscarriage in a 33-year-old primigravida at the 24 th week of gestation. An emergency laparotomy showed spontaneous rupture of the left uterine artery and bowel wall endometrioma. Artery suture, bowel resection and cesarean section on demised fetus were performed. Conclusions: Although pregnancy may have beneficial effects on endometriosis, rare but significant endometriosis-associated pregnancy complications may also occur.